Characterization of tool wear when machining Alloy 718 with high pressure cooling using conventional and surface-modified WC–Co tools - Hoier, P.; Klement, U.; Tamil Alagan, N.; Beno, T.; Wretland, A. (Сверхтвердые материалы, 2017)
Coolant supplied by high pressure into the cutting zone has shown the lower thermal loads on the tool when machining difficult-to-cut materials as the Alloy 718. In this study, we investigate how the combination of high-pressure cooling and tool-surface modifications can lead to further improvements regarding tool life. The general approach is to enhance the coolant-tool interaction by increasing the contact area. Therefore, we machined cooling features into flank and rake faces of commercially available cemented tungsten carbide inserts. In this way, the surface area was increased by ~ 12 %. After the cutting tests, the tools were analyzed by scanning electron microscopy combined with energy-dispersive X-ray spectroscopy. Compared with conventional tools, the tool modifications reduced the flank wear by 45 % for the investigated cutting parameters. Furthermore, we were able to significantly increase the cutting speed and feed rate without failure of the tool. The investigated surface modifications have great potential to enhance the productivity of metal cutting processes.